2015
DOI: 10.17161/iallt.v45i1.8550
|View full text |Cite
|
Sign up to set email alerts
|

Implementing and Managing Online Exensive Reading

Abstract: Smartphones, tablets, and today's touch screen laptops are powerfultools capable of serving hundreds of specialized, complex operationsand applications to anyone, seemingly anywhere in the world. Forsecond language learners and those who teach them, these toolssuddenly have the potential to recast the reading experience for 21stcentury students and invigorate Extensive Reading (ER) research.Exploration into digital ER exclusively through the medium of mobiledevices is only an emerging area of study in the Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 13 publications
3
15
2
Order By: Relevance
“…A study conducted by Cote & Milliner (2015) showed a different result than the previous one. The study was also conducted in Japan to determine the students' attitudes towards the program and how XReading influences their reading speed and TOEIC scores.…”
Section: Introductioncontrasting
confidence: 58%
“…A study conducted by Cote & Milliner (2015) showed a different result than the previous one. The study was also conducted in Japan to determine the students' attitudes towards the program and how XReading influences their reading speed and TOEIC scores.…”
Section: Introductioncontrasting
confidence: 58%
“…It provides them more privileges in borrowing graded readers and gives them access to teacher's feedbacks on their reading performance and individual progress. According to the study of Cote & Milliner (2015), they found that using XReading can change students' preferences in reading platform from paperback to online book. Further, XReading can give students more flexibility on time, place, and frequency of reading.…”
Section: Trends and Possibilities In Extensive Readingmentioning
confidence: 99%
“…Due to teachers' demanding work, they can hardly find time to confirm whether students have really read the book or not. Third, ER is not a part of the language curriculum (Cote & Milliner, 2015). Having it isolated from curriculum and examination makes teachers and students not to take it seriously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, creating a space for ER in a heavy-loaded curriculum and designing customized ER activities for varied learners also seem difficult for untrained teachers (Maley, 2009). Lastly, efficiently monitoring English reading progress, giving timely feedback to students (Cote & Milliner, 2015), and balancing the pressure of national exams with ER activities seem taxing for already overburdened and exhausted teachers.…”
Section: Review Of the Literaturementioning
confidence: 99%